2017
DOI: 10.1016/j.juro.2017.01.059
|View full text |Cite
|
Sign up to set email alerts
|

Penile Cancer: Contemporary Lymph Node Management

Abstract: Recent developments in lymph node management have occurred in penile cancer, such as minimally invasive lymph node diagnosis and intervention strategies. These advances have been met with a degree of controversy in the contemporary literature. Current data suggest that dynamic sentinel lymph node biopsy provides excellent sensitivity and specificity for detecting lymph node metastases. More robust long-term data on multicenter patient cohorts are required to determine the optimal management of lymph nodes in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 49 publications
2
37
0
1
Order By: Relevance
“…In contrast to local recurrence patterns, regional recurrence (10.3%) and/ or distant metastasis (13.8%) were more frequent in those patients treated with partial or total penectomy, which is most likely due to the fact that patients who underwent (partial) penectomy had a higher primary tumor staging (≥ pT2: 44.8% vs. 11.5%) with increased positive inguinal lymph node status at primary invasive nodal staging (36.4% vs. 0%), thus being at higher risk for distant cancer spread on follow-up. Previous studies have shown that narrow surgical resection margins of only a few millimeters are sufficient to control local disease without affecting OS [39,40], so that penile-preserving surgery can spare a considerable amount of tissue [21,22] allowing a paradigm shift towards more organ-sparing approaches. Whichever surgical technique is chosen to manage the primary tumor lesion, lymph node management should be based on the recommended guidelines [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to local recurrence patterns, regional recurrence (10.3%) and/ or distant metastasis (13.8%) were more frequent in those patients treated with partial or total penectomy, which is most likely due to the fact that patients who underwent (partial) penectomy had a higher primary tumor staging (≥ pT2: 44.8% vs. 11.5%) with increased positive inguinal lymph node status at primary invasive nodal staging (36.4% vs. 0%), thus being at higher risk for distant cancer spread on follow-up. Previous studies have shown that narrow surgical resection margins of only a few millimeters are sufficient to control local disease without affecting OS [39,40], so that penile-preserving surgery can spare a considerable amount of tissue [21,22] allowing a paradigm shift towards more organ-sparing approaches. Whichever surgical technique is chosen to manage the primary tumor lesion, lymph node management should be based on the recommended guidelines [5].…”
Section: Discussionmentioning
confidence: 99%
“…Whichever surgical technique is chosen to manage the primary tumor lesion, lymph node management should be based on the recommended guidelines [5]. Primary DSNB in patients with ≥ pT1G2 without palpable inguinal lymph nodes has matured into a reliable staging method with lower morbidity rates than rLND [5,38,39]. To ensure a good long-term oncological outcome with early detection of local recurrence, organ-preserving surgery needs a good patient compliance and should always be followed by careful patient management with regular physician and self-investigation, and regular oncological follow-up visits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geographical flexibility provided by residents who are spread over regions allows access to a wide range of different practices which can increase the generalisability of the results and provide large samples sizes that are powered to investigate associations and disease areas that may otherwise be difficult to. Types of research projects that work well within resident-led collaboratives are observational cohort studies [1,2], case-control studies [3], systematic reviews [4][5][6], meta-analysis [7], and randomised controlled trials [8][9][10].…”
mentioning
confidence: 99%
“…It has also incorporated the development of, and is freely available to, medical students. Providing an avenue for ease of access to contributions in current projects, in addition to a communication nexus where questions are answered and advice is given by senior researchers who have experience within the field of Urology research.Despite its infancy, early successes can be seen in YURO's involvement in several publications [3][4][5]. In addition to regular education sessions with medical students and perhaps most importantly, an ongoing dialogue between junior members interested in improving their research methods and experienced members interested in sharing their wisdom.…”
mentioning
confidence: 99%